Use of outcome measures in children with severe cerebral palsy: A survey of U.K. physiotherapists. (6th June 2019) - Knox, Virginia; Vuoskoski, Pirjo; Mandy, Anne
Abstract: Objectives: To investigate the use of outcome measures for children with cerebral palsy (CP) by paediatric physiotherapists (PTs) who are based in the United Kingdom, as limited research exists regarding their use in this population, and to explore therapists' use of measures within different Gross Motor Function Classification System (GMFCS) levels and for different types of CP. Methods: A six‐item online survey was advertised through two paediatric therapy special interest groups inviting physiotherapists to participate. Descriptive statistics (range, frequencies, and percentages) were used to analyse survey data. Results: Two hundred and seven physiotherapists returned completed survey questionnaires. One hundred and seventy‐six (85%) therapists reported using a wide variety of outcome measures (57). Eighty‐one per cent of therapists' responses for having "most difficulty" in identifying responsive outcome measures were for children with impaired mobility at GMFCS Levels IV–V and children with more significant body involvement (76%), for example, spastic quadriplegia or dyskinesia. Eighty‐six per cent of therapists' responses for having "greatest ease" of identifying responsive outcome measures were for children within GMFCS Levels I–III and for children with less significant body involvement (72%), for example, hemiplegia. The variety of outcome measures used by therapists with children within GMFCS IV–V was less (16). Conclusions: The majority (85%) of the PTs surveyed used outcome measures with children with CP, but 81% perceived a difficulty in identifying responsive measures for children with more severe impairments who are classified as GMFCS IV–V. The reasons for this perceived difficulty warrant investigation and may suggest a need for training regarding relevant measures and/or a need to develop new measures for this group of children.